Research progress on protective effect of polysaccharide from traditional Chinese medicine on myocardial ischemia-reperfusion injury - Qian Sun; Hongtian Fei; Siqi Zhao; Lijiao Zhang; Rui Fei (Guoji laonian yixue zazhi)
Myocardial ischemia-reperfusion injury (MIRI) is a prevalent pathophysiological process associated with ischemic heart disease and significantly exacerbates myocardial damage, particularly in the elderly population.This condition not only poses serious risks to individual health but also brings creates substantial societal and economic burdens.Polysaccharides, natural macromolecule found in animals, plants and microorganisms, serve as active substance that confer various health benefits.Among these, polysaccharides extracted from traditional Chinese medicine(TCM) through modern scientific techniques have gained prominence in the medical field due to their safety and high efficiency, playing a vital role in the management of various cardiovascular diseases.This paper, provides a comprehensive review of the role and mechanisms of TCM-derived polysaccharide in MIRI, aiming to furnish valuable insights for the future treatment of cardiovascular diseases in the elderly.